2010
DOI: 10.1161/hypertensionaha.109.146399
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-17β and Its Cytochrome P450- and Catechol- O -Methyltransferase–Derived Metabolites Stimulate Proliferation in Uterine Artery Endothelial Cells

Abstract: Abstract-Estradiol-17␤ (E 2 ␤) and its metabolites, which are sequentially synthesized by cytochrome P450s and catechol-O-methyltransferase to form 2 and 4-hydroxyestradiol (OHE 2 ) and 2-and 4-methoxestradiol (ME 2 ), are elevated during pregnancy. We investigated whether cytochrome P450s and catechol-O-methyltransferase are expressed in uterine artery endothelial cells (UAECs) and whether E 2 ␤ and its metabolites modulate cell proliferation via ER-␣ and/or ER-␤ and play roles in physiological uterine angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
96
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(109 citation statements)
references
References 44 publications
8
96
0
5
Order By: Relevance
“…In these studies we reported local uterine, but not systemic omental artery (OA) or renal artery (RA) effects of pregnancy-specific alterations, including elevations in specific levels of estrogen receptoralpha (ER-α) and ER-β, angiotensin II type-1 receptor expression, soluble and particulate guanylate cyclases, and pregnancy-enhanced activation of endothelial nitric oxide synthase [28][29][30][31][32][33][34], demonstrating locally increased endothelial vasodilatory sensitivity to several specific hormones during gestation. Moreover, using a validated in vitro uterine artery endothelial cell (UAEC) pregnancy model, we noted pregnancy-specific estrogen, as well as estrogen metabolites, stimulated proliferative responses in pregnant UAECs (P-UAECs), but not nonpregnant (NP-UAECs) demonstrating angiogenic cellular programming is maintained in primary culture through multiple passages [35]. However, little is known concerning the local uterine versus systemic changes of UAendo and UAvsm expression of LEPR in pregnancy or in regulating UA angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies we reported local uterine, but not systemic omental artery (OA) or renal artery (RA) effects of pregnancy-specific alterations, including elevations in specific levels of estrogen receptoralpha (ER-α) and ER-β, angiotensin II type-1 receptor expression, soluble and particulate guanylate cyclases, and pregnancy-enhanced activation of endothelial nitric oxide synthase [28][29][30][31][32][33][34], demonstrating locally increased endothelial vasodilatory sensitivity to several specific hormones during gestation. Moreover, using a validated in vitro uterine artery endothelial cell (UAEC) pregnancy model, we noted pregnancy-specific estrogen, as well as estrogen metabolites, stimulated proliferative responses in pregnant UAECs (P-UAECs), but not nonpregnant (NP-UAECs) demonstrating angiogenic cellular programming is maintained in primary culture through multiple passages [35]. However, little is known concerning the local uterine versus systemic changes of UAendo and UAvsm expression of LEPR in pregnancy or in regulating UA angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, estrogen-induced angiogenesis has also been attributed to changes in eNOS, thrombospondin, and free radical generation, making it tempting to speculate that CYP1B1 may actually mediate the effects of the hormone. Certainly, the CYP1B1-derived metabolites of b-estradiol promote angiogenesis in uterine artery endothelial cells (Jobe et al, 2010). Rather intriguingly, residues 41-48 of human CYP1B1 are part of a mitochondrial import signal and the cleavage of CYP1B1 by serine proteases results in its targeting to mitochondria, which is associated with oxidative stress and mitochondrial dysfunction (Bansal et al, 2014).…”
Section: Inflammation and Resolution Of Inflammationmentioning
confidence: 99%
“…Estrogens formed by placental aromatase may enhance angiogenesis, uteroplacental blood flow, and reduce systemic vascular resistance (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%